Report of the second international conference on next generation sequencing for adventitious virus detection in biologics for humans and animals. (September 2020) - Khan, Arifa S.; Blümel, Johannes; Deforce, Dieter; Gruber, Marion F.; Jungbäck, Carmen; Knezevic, Ivana; Mallet, Laurent; Mackay, David; Matthijnssens, Jelle; O'Leary, Maureen; Theuns, Sebastiaan; Victoria, Joseph; et al.
Abstract: The IABS-EU, in association with PROVAXS and Ghent University, hosted the "2 nd Conference on Next Generation Sequencing (NGS) for Adventitious Virus Detection in Human and Veterinary Biologics" held on November 13 th and 14 th 2019, in Ghent, Belgium. The meeting brought together international experts from regulatory agencies, the biotherapeutics and biologics industries, contract research organizations, and academia, with the goal to develop a scientific consensus on the readiness of NGS for detecting adventitious viruses, and on the use of this technology to supplement or replace/substitute the currently used assays. Participants discussed the progress on the standardization and validation of the technical and bioinformatics steps in NGS for characterization and safety evaluation of biologics, including human and animal vaccines. It was concluded that NGS can be used for the detection of a broad range of viruses, including novel viruses, and therefore can complement, supplement or even replace some of the conventional adventitious virus detection assays. Furthermore, the development of reference viral standards, complete and correctly annotated viral databases, and protocols for the validation and follow-up investigations of NGS signals is necessary to enable broader use of NGS. An international collaborative effort, involving regulatory authorities, industry, academia, and other stakeholders is ongoing toward this goal. Highlights: NGS can be as sensitive for virus detection as PCR assays; it can be used as a replacement assay. NGS can broadly detect viruses and be standardized and validated; it has the potential to substitute animal-based assays. NGS can supplement and could potentially replace in vitro cell culture assays based on suitability and assay comparison. Further work is needed on strategies for distinguishing true and false positive results and managing inconclusive results.